Outcome of total proctocolectomy with ileal pouch-anal anastomosis for ulcerative colitis - Cho, Wontae (The Korean Surgical Society, 2012)
PURPOSE: We evaluated the risk factors for late complications and functional outcome after total proctocolectomy (TPC) with ileal pouch-anal anastomosis (IPAA) for ulcerative colitis (UC). METHODS: Pre- and postoperative clinical status and follow-up data were obtained for 55 patients who underwent TPC with IPAA between 1999 and 2010. The median follow-up duration was 4.17 years. Late complications were defined as those that appeared at least one month after surgery. For a functional assessment, telephone interviews were conducted using the Global Assessment of Functioning Scale. Twenty-eight patients completed the interview. RESULTS: Late complications were found in 20 cases (36.3%), comprising pouchitis (n = 8), bowel obstruction (n = 5), ileitis (n = 3), pouch associated fistula (n = 2), and intra-abdominal infection (n = 2). The preoperative serum albumin level for patients with late complications was lower than for patients without (2.4 ± 0.5 vs. 2.9 ± 0.7, P = 0.04). Functional outcomes were not significantly associated with clinical characteristics, follow-up duration, operation indication, or late complications. CONCLUSION: This study demonstrated that a low preoperative albumin level could be a risk factor for late complications of TPC with IPAA. Preoperative nutritional support, especially albumin, could reduce late complications. Functional outcomes are not related to late complications.